Short-term feeding with high fructose diet impairs bone mineralization in growing rats - Manterys, Angelika; Filipiak-Florkiewicz, Agnieszka; Florkiewicz, Adam; Franczyk-Zarow, Magdalena; Kus, Edyta; Sady, Marek; Kostogrys, Renata B. (Progress in Nutrition, 2018)
Aim: The objective of this study was to investigate effects of short-term, high fructose intake on mineralization and biomechanical strength of bones in growing rats. Methodology: Male Wistar rats (aged 8 weeks) were divided into two experimental groups. Animals were fed with AIN 93G diet or high fructose diet, containing 63 wt% of fructose, for four weeks. Bone calcium and phosphorus content were determined according to PN-EN 15505:2009 norm and AOAC 986.24-1988 method, respectively. The bones biomechanical strength was tested using texture analyzer. Results: Feeding rats with high fructose diet resulted in significant (p<0,05) decrease of calcium content in femur and tibia. Also phosphorus content was significantly (p<0,05) decreased in femoral bone from animals fed high fructose diet. The biomechanical strength of femur and tibia was slightly lower in high fructose group compared to control. Conclusion: Short-term high fructose intake impairs calcium and phosphorus bone deposition in growing animals.